Intermittent Massage as a Therapeutic Option for Compartment Syndrome after Embolectomy of the Lower Limbs - José Maria Pereira de Godoy; Maria de Fátima Guerreiro Godoy (Case Reports in Vascular Medicine)
The case of a 54-year-old cardiac patient is reported, who was admitted to hospital with a complaint of sudden pain in the legs associated with edema, paresthesia, and coldness. Arterial embolism of the lower limbs was diagnosed and the patient was submitted to bilateral embolectomy. The patient evolved with a burning sensation, hypersensitivity in the right leg, swelling, and difficulty bending and stretching the sole of the foot and the knee. A physical examination detected edema and increased tension in the anterior, lateral, and posterior compartments. Treatment using intermittent massage of the leg during the evaluation of the patient was chosen in an attempt to stimulate lymphatic and venous drainage. After a few minutes of stimulation, there was significant improvement in the pain and edema. In 40 minutes, there was total reduction of the pain in the posterior and lateral compartments and improvement of over 50% in the anterior compartment. After this, the patient started to bend the knee without pain and bend the sole of the foot with slight pain. On the following day, the patient was walking around the hospital ward without difficulty. It seems that intermittent massage is a therapeutic option in selected cases of compartment syndrome.